PENGARUH TIPE INDUSTRI, UKURAN PERUSAHAAN, LIKUIDITAS, SOLVABILITAS, PROFITABILITAS, LEVERAGE DAN UKURAN DEWAN KOMISARIS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Retno Wati, 13.05.52.0010; Poerwati, Tjahjaning (Students Journal of Accounting and Banking, 2017)
The purpose of this study is to examine the influence of Industry Classification, Firm Size, Liquidity, Solvency, Profitability, Leverage, and size of Board of Commissioner to Corporate Social Resposibility Disclosure in Manufacturing Companies listed on the Indonesia Stock Exchange. The dependent variable is Corporate Social Resposibility Disclosure. Independent variable are Industry Classification, Firm Size, Liquidity, Solvency, Profitability, Leverage, and size of Board of Commissioner. The population in this study was all Manufacturing Company listed on the Indonesia Stock Exchange in 2012-2015. Samples were 356 manufacturing companies. This study used purposive sampling method.The analysis used in this reseacrh are multiple linear regression analysis. The results of the testing of hypotheses partial evaluation shows that there are significant influence on Firm Size, Leverage, Profitability and size of Board of Commisioner, while for Industry Classification, Liquidity and Solvency not have significant influence to the Corporate Social Responsibility Disclosure.Keywords: Industry Classification, Firm Size, Liquidity, Solvency, Proftitability, Leverage, Size of Board of Commissioner, Corporate Social Resposibility Disclosure